2003
DOI: 10.1590/s0103-50532003000400012
|View full text |Cite
|
Sign up to set email alerts
|

Effect of carboxylate compounds on the electrochemical behavior of dopamine at a mercury electrode

Abstract: A oxidação eletroquímica da dopamina leva à deposição de filmes poliméricos sobre a superfície de eletrodos sólidos, diminuindo a atividade dos mesmos. No eletrodo de mercúrio o processo redox ocorre na região de potencial de oxidação do mercúrio. No entanto, na presença de compostos carboxílicos o voltamograma cíclico da dopamina, no eletrodo de mercúrio, é diferenciado e apresenta um novo produto eletroativo proveniente do processo de oxidação da dopamina. O presente trabalho descreve resultados preliminares… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Otherwise, comparing the properties of the carboxylic groups of the 4PA-BDD surface with those of the carboxylic and hydroxyl groups that are probably present on the O-BDD surface, the electrostatic interactions of these groups with the analytes (DA and AA) should be significantly stronger for 4PA-BDD. These interactions would be expected to lead to sufficient resolution of the DA and AA peaks, with faster electron transfer for DA oxida- [41]. Such a complex is expected to be formed in the case of 4PA, because a PBS solution containing DA and 4PA remained colorless after storage for 3 days in ambient air, while a DA solution without 4PA turned brown within 30 min.…”
Section: Electrochemical Amplification Of Da Oxidation At the 4pa-bddmentioning
confidence: 99%
“…Otherwise, comparing the properties of the carboxylic groups of the 4PA-BDD surface with those of the carboxylic and hydroxyl groups that are probably present on the O-BDD surface, the electrostatic interactions of these groups with the analytes (DA and AA) should be significantly stronger for 4PA-BDD. These interactions would be expected to lead to sufficient resolution of the DA and AA peaks, with faster electron transfer for DA oxida- [41]. Such a complex is expected to be formed in the case of 4PA, because a PBS solution containing DA and 4PA remained colorless after storage for 3 days in ambient air, while a DA solution without 4PA turned brown within 30 min.…”
Section: Electrochemical Amplification Of Da Oxidation At the 4pa-bddmentioning
confidence: 99%
“…In this case, the solutions that contain carboxylate groups give rise to lower peak currents, while nearly identical currents are observed with the chloride and sulfateÀcontaining solutions. It is known that the electrochemistry of DA is influenced by the presence of carboxylate anions, and although this is poorly understood, it has been suggested that the carboxylic anions form a product with the DA oxidation species [37]. The MES buffer gives the lowest peak current and this is probably related to the low conductivity of this buffering system.…”
Section: Detection Of Dopamine At Ppyàsβcdmentioning
confidence: 99%
“…Ascorbic acid gave a negative interference (80% in equal molar ratio with dopamine) presumably due to the reaction with hydrogen peroxide, thus this is a serious interferent for direct analysis. To overcome this problem many different strategies have been proposed, such as: the use of a nafion membrane, that repels ascorbic acid and other negatively charged species, 59 the use of the multivariate calibration methods, 60 the addition of ethylenediaminetetraacetate in the supporting electrolyte 61,62 or addition of ascorbate oxidase enzyme. 63 An interference of 62% for molar ratios higher than 150 was observed for sodium bisulfite.…”
Section: Sensor Application: Interferents Recovery and Analysis Of Pmentioning
confidence: 99%